Progressive myoclonic ataxia associated with coeliac disease. The myoclonus is of cortical origin, but the pathology is in the cerebellum. - Bhatia, K; Brown, P; Gregory, R; Lennox, G; Manji, H; Thompson, P; Ellison, D; Marsden, C (1995)
We report four patients with a progressive myoclonic ataxic syndrome and associated coeliac disease. The onset of the neurological syndrome followed the gastrointestinal and other manifestations of coeliac disease while on a gluten-free diet, in the absence of overt features of malabsorption or nutritional deficiency. The condition progressed despite strict adherence to diet. The neurological syndrome was dominated by action and stimulus sensitive myoclonus of cortical origin with mild ataxia and infrequent seizures. Plasmapharesis and immunosuppressive treatment were tried in two patients but were not beneficial. Post-mortem examination of the brain in one case showed selective symmetrical atrophy of the cerebellar hemispheres with Purkinje cell loss and Bergmann astrocytosis, and with preservation of the cerebral hemispheres and brainstem. Coeliac disease should be considered in the differential diagnosis of all patients presenting with a progressive myoclonic ataxic syndrome.